Optimization of SAMR model scaffolding for the development of descriptive writing skills - La Ode Nggawu; Nurindah Nurindah; Anugrah Puspita Ayu Muhammad; Waode Ade Sarasmita Uke; Nurul Atma; Wahyudin Madil; Nguyen Thi Phuong Thao; Minerva Apita-Chavez (International Journal of Evaluation and Research in Education (IJERE), 2026)
This research presents an investigation of how the application of the digital substitution, augmentation, modification, redefinition (SAMR)-based scaffolding might be used to support first-semester basic writing students in overcoming challenges related to grammar proficiency and descriptive writing. A mixed-methods sequential explanatory design was used with 40 students enrolled in English language courses. Quantitative data were obtained through a 14-item Likert-type questionnaire measuring SAMR integration and challenges faced, while qualitative analysis was conducted on semi-structured interview data using NVivo to code thematically. The scores for all implementation indicators indicate that high average values were obtained (global M=3.37), indicating that SAMR-based activities and scaffolding were viewed as useful and engaging for supporting descriptive writing. The level of challenges was perceived as low to moderate (mean=2.59 overall). The key issues were that lecturers needed to offer more consistent support, access to devices was restricted, and students had uneven digital skills. Thematic results identified growth in grammatical consciousness, development of short texts, and creativity as projects that resulted in multimodal outcomes and student involvement. The research also underscores the importance of strong institutional structures and continued support for teaching. It concludes that employing SAMR-informed digital scaffolding is a strategy with the potential to support writing instruction through technology.